2001
DOI: 10.1002/ana.10059
|View full text |Cite
|
Sign up to set email alerts
|

Novel heteroplasmic mtDNA mutation in a family with heterogeneous clinical presentations

Abstract: The protean manifestations of a novel maternally inherited point mutation of the mitochondrial genome are reported. The proband showed isolated, spastic paraparesis. A brother, who had suffered from a multisystem progressive disorder, ultimately died of cardiomyopathy. Another brother is healthy. The proband's mother showed truncal ataxia, dysarthria, severe hearing loss, mental regression, ptosis, ophthalmoparesis, distal cyclones, and diabetes mellitus. A muscle biopsy performed in the proband failed to show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 20 publications
0
31
0
Order By: Relevance
“…Adult-onset spastic paraparesis is a feature that is rarely associated with mtDNA disease (26,27); however, our patient had progressive lower limb spasticity. This spasticity might be attributable to axonal and myelin degeneration and loss affecting the left anterior limb and genu of the internal capsule.…”
Section: Discussionmentioning
confidence: 84%
“…Adult-onset spastic paraparesis is a feature that is rarely associated with mtDNA disease (26,27); however, our patient had progressive lower limb spasticity. This spasticity might be attributable to axonal and myelin degeneration and loss affecting the left anterior limb and genu of the internal capsule.…”
Section: Discussionmentioning
confidence: 84%
“…Lin Z, et al [12] found G8584A mtDNA mutation may influence LVH in hypertensives. In particular, several point mutations such as G4284A [13] , A4295G [14] , A4269G [15] , A4317G [15] and A4300G [16] located in tRNA Ile contribute to hypertrophic cardiomyopathy to certain degree. A systematic and extended mutational screening for the mitochondrial genome has been initiated in a large cohort of Chinese population by the Geriatric Cardiology Clinic at the Chinese PLA General Hospital, Beijing, China.…”
Section: Mtdna Mutationsmentioning
confidence: 99%
“…The mutation load was approximately 55%, 80% and 90% in the muscle DNA of the patient, his mother and his affected brother respectively. 268 …”
Section: The Clinical Phenotypes Of Mitochondrial Trna Mutationsmentioning
confidence: 99%